Effect of Vitis gracilis Wall (gagatan harimau) in the recovery of gastrocnemius muscle cells and cytochrome c expression of Mus musculus - Nila Zusmita Wasnis; Syafruddin Ilyas; Salomo Hutahaean; Ramlan Silaban; Putri C. Situmorang (GarVal Editorial Ltda., 2022)
Context: Physical exercise with maximum intensity to fatigue can cause impaired immunity. Gastrocnemius muscle damage is found in eccentric activities in sports. Vitis gracilis has been proven as a healing agent for degenerative diseases. Aims: To determine whether the V. gracilis Wall extract can recovery of gastrocnemius muscle cells of Mus musculus through reduced inflammatory cells and cytochrome c expression. Methods: The studies turned into performed in 5 groups of remedies withinside the study. The remedy groups consisted of T1: Negative control (no treatment), T2: Positive control (Swim Until the First Sink/SUFS) + Vit. C 0.2 mg/kg BW, T3: SUFS + 50 g/kg BW of V. gracilis, T4: SUFS + 75 g/kg BW of V. gracilis and T5: SUFS + 100 g/kg BW of V. gracilis. Mice were dissected and then the leg were taken for analysis of gastrocnemius muscle cells in immunohistochemistry. Results: There was a significant difference (p<0.01) using the ANOVA one-way test on inflammatory cells in gastronomeus muscle tissue of Mus musculus and cytochrome c expression. V. gracilis 100 mg/kg BW can repair and reduce inflammatory cells in the gastronomic muscle tissue. The expression of cytochrome c protein becomes weaker when it is increased. Conclusions: V. gracilis can recover gastrocnemius muscle cells of Mus musculus through reduced inflammatory cells and cytochrome c expression because of swim exercise.